Physical and mechanical properties of cement-bonded particleboards produced at different water pre-treatment temperatures and cement/wood mixing ratios (2011)
The influences of water pre-treatment temperature and cement/wood mixing ratios on static and moisture response properties of cement-bonded particleboards produced from mixed Nigerian hardwood species were assessed in this study. The process variables for board fabrication were pre-treatment temperature (5 levels) and wood/ cement mixing ratios (5 levels) resulting in 25 treatment combinations in a factorial experiment. The examined properties are modulus of rupture (MOR), modulus of elasticity (MOE), water absorption (WA), thickness swelling (TS) and linear expansion (LE) properties of the experimental cement-bonded particleboards. Data collected were analysed using a combination of ANOVA and multiple linear regression models. Mean MOR and MOE ranged from 4.02 to 12.74 N/mm2 and 2040 to 4060N/mm2 respectively, while (WA), (TS) and (LE) ranged from 27.13 to 43.97%, 0.51 to 3.50% and 0.14 to 0.72% respectively. Strength (MOR) and stifness (MOE) of the boards increased as water pre-treatment temperature were raised from 35°C to 80°C. As water pre-treatment temperature was raised from 80°C to 95°C, weaker and inferior boards were produced. Water pre-treatment temperature was weakly correlated with MOR, MOE, WA, TS and LE. On the other hand, cement/wood mixing ratio was well correlated with these board properties. The study thus demonstrated that there is optimum water pretreatment temperature range (65°C-80°C) within which high quality boards can be produced in the selected species; and beyond which board quality will be impaired.